GENETIC VARIATIONS AMONG AQUILARIA SPECIES AND GYRINOPS VERSTEEGII USING AMPLIFIED FRAGMENT LENGTH POLYMORPHISM MARKERS - NURITA TORUAN-MATHIUS; DEWI RAHMAWATI; ANIDAH (SEAMEO BIOTROP, 2009)
Aquilaria sp Thymelaeaceae is the most valuable non wood production of forestry plant in Indonesia It produces a fragrant resin when subjected to fungal attack and has been traded internationally known as gaharu Knowledge of genetic diversity and relationship among species and genus is important for breeding purposes and species conservation In this study genetic variability of six Aquilaria species were analyzed using the AmplifiedFragment Length Polymorphism AFLP markers Ten AFLP primer combinations amplified 1353 DNA fragments ranging in size from100 to 350 bp of which 1285 95 of them were polymorphic Genetic similarities among Aquilaria sp consisted of A malaccensis A beccariana A microcarpa and A crassna ranged from 6390 to 7200 based on Dice coefficient The dendrogram derived by the unweighted pair group method with arithmetic mean of germplasm analysiswere clustered into two main groups Hence a genetic variation among species is quiet high Bootstrap values for the groups supported 70 of the cluster using a linear relationship equation of r 0724 P 00001 was observedbetween known pedigrees and AFLPderived genetic similarity for 136 pairwise comparisons of Aquilaria species For example A malacensis and A microcarpa have the highest genetic similarity 7200 compared with another Aquilaria species Primer pairs EACGMCTA produced a specific fragment for A beccariana 850 bp A crasna 550 bp 180 bp and 140 bp A malaccencis 1500 bp A microcarpa 250 bp and Gyrinops versteegii 150 bp Primer pairs EACGMCAA produced a specific DNA fragment only for A beccariana 1500 bp and 100 bp Primer pairs EACCMCAC also produced only specific fragment for A crassna 1500 bp Study showed the usefulness of AFLP analysis in Aquilaria sp and its potential application for breeding and species conservation Further molecular diversity estimated in the present study combined with the datasets on other morphologicalagronomic traits will be useful for selecting the appropriate accessions for plant improvement through conventional and molecular breeding approaches.Key words Gaharu Aquilaria sp Gyrinops sp genetic diversity molecular marker amplifiedfragment length polymorphism AFLP